A review, critique, and analysis of the literature concerning the likelihood of women being employed in expatriate international business management positions - Wong, Swee Wei (Auckland University of Technology, 2005)
A gap has been identified in that women were found to have been under-represented in international business since the 1980s, when compared to their male counterparts. As international business becomes more important, the number of women expatriates is increasing at a slow pace. As a result, it is the purpose of this study to look at the likelihood of women being employed in expatriate positions. Previous studies were undertaken based on the three major myths proposed by Adler (1984a; 1984b; 1984c), which are: (1) Women are unwilling to undertake international assignments; (2) Multinational companies are reluctant to send women on overseas assignments; and (3) Prejudice of some foreigners or human resource (HR) managers against the competency of women expatriates. Given the evidence and findings by researchers in this field, the first myth is untrue because women are proved more willing to accept overseas assignments. However, the other two myths: multinational corporations are reluctant to send women abroad, and the prejudices of some foreign cultures or HR managers towards the competencies of women expatriates, still hold true. This study suggests that if the stereotypes towards the competencies of women expatriates are not resolved, women will be given fewer opportunities to be involved in international assignments. While the competencies of women expatriates are readily observable, obvious inequalities towards their employability into international business management positions still exist, ensuring that this issue continues to be of importance to HR policy makers. This study recommends that HR policies should be enhanced in order to promote fairer and equal practices in the organisation. Having a better policy in place would increase the possibilities of qualified and competent women being employed in international business management positions. This would therefore maximise the effectiveness of international assignments, and eventually lead to a competitive advantage in the global market.
Keywords: Businesswomen; Women executives